PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATERI EKOSISTEM DI SMP BUMI KHATULISTIWA - Fauziah, Nurseri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study was purposed to see the influence of problem based learning model towards students learning outcome on the material of ecosystem in 7th grade Bumi Khatulistiwa Junior High School. The form of this study was quasi experimental design with nonequivalent control group design. The sample of this study was class 7th A (control class) and class 7th B (experiment class). Sample selection technique in this study using the saturation sampling technique in which all members of the population was used as sample. The instrument used in this study was 20 questions of multiple choice test. The average of students’ learning outcome who taught using problem based learning model was 18.47 higher compared with the average of students’ who taught using conventional model that was 16.38. Based on U Mann Whitney test, obtained Zcount < -Ztable (-3.17 < -1.96), which mean that there was significant difference between the students’ learning outcome who taught using problem based learning and conventional model. The obtained effect size value was 1.11 which mean that the influence of problem based learning model towards students’ learning outcome was high and contributes 36.65%. Keywords: problem based learning model, material of ecosystem, learning outcome